Depression among Healthcare Workers during the Pandemic: The Faultless Fundamentals - Khare, Sumit (International Journal of Nursing Research, 2023)
Coronavirus disease 2019 (COVID-19) caused due to a novel coronavirus (serious acute respiratory syndrome-CoV-2) has impacted lives of millions of people around the globe in the past year. To reduce the spread of coronavirus, people were enforced to stay indoors, maintain social distancing, and wear a mask. On today’s date, a huge coronavirus vaccination drive is being carried out to vaccinated maximum amount of people to keep the spread of the virus at bay. The pandemic has shown increased anxiety, distress, and mental health problems among people around the world due to fear of contracting the virus, its increasing spread, economic loss, lack of a routine, and uncertainty of the future. According to recent report, depression in India is reported to be 25% due to the pandemic which calls for an increased need of preventive and curative measures for mental health problems. The population most affected due to the COVID-19 pandemic were the frontline healthcare professionals (HCPs) trying to tackle the COVID-19 infection which do not have any specific treatment or medication. This has certainly put the HCPs under an extreme stress which has shown to have many ill effects on their mental as well as physical well-being resulting in depression, anxiety, stress, insomnia, etc. The major stressors for HCPs were increased burden of workload, exhaustion, unavailability of essential equipment, pressure out of making ethically difficult decisions, and no social life. This review provides the epidemiology of COVID-19, its impact, its psychological effect on the general population and on HCPs, and some suggestive measures.